The study of interface shear strength between geotextile and soil liner containing with different percentage of sodium bentonite / Nor Azizah Che Azmi - Che Azmi, Nor Azizah (2013)
The purposed of this research is to focus on the interface shear strength between geotextiles and soil with different percentage of sodium bentonite. Firstly, the physical properties of the soil sample must be identified in orderr to determine the soil classification. The laboratory test includes atterberg limit test, shrinkage limit test, specific gravity test, pH test, sieve analysis test and hydrometer test. The soil samples which are natural soil sample, soil added with 0% of sodium bentonite, soil added with 2.5% of sodium bentonite, soil added with 5.0% of sodium bentonite, soil added with 7.5% of sodium bentonite and soil added with 10% of sodium bentonite. Based on the result, the percentage of sodium bentonite did not give good relationship to the soil samples such liquid limit test, plastic limit test, plasticity index and specific gravity as the value that obtained quite similar and did not increased when increasing percentage of sodium bentonite. After the soil is classified, the next test was compaction test. The puipose of the compaction test is to get the value of optimum moisture content that need to be applied during direct shear box test. However, the value for compaction and direct shear test also did not give good result as the value for optimum moisture content, cohesion and friction angle also quite similar to each other thus, it can be clearly said that the percentage of sodium bentonite did not give effect to the soil samples and not suitable to be use in this type of soil.